Komunikasi Kebencanaan Badan Penanggulangan Bencana Daerah (BPBD) dalam Mitigasi Krisis Kebakaran pada Masyarakat Simeulue Timur - Fitri Meliya Sari; Dhiva Chintya (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This research aims to analyze the disaster communication strategies of the Regional Disaster Management Agency (BPBD) of Simeulue Regency in mitigating fire crises in East Simeulue District, identify community responses to mitigation messages, and examine the supporting and inhibiting factors affecting the effectiveness of disaster communication. The research uses a descriptive qualitative approach with data collection techniques thru observation, in-depth interviews, and documentation. Informants were purposively selected, including elements from BPBD, village officials, community leaders, and the people of East Simeulue. Data analysis used the interactive model of Miles and Huberman, while data validity was tested thru triangulation of sources, techniques, and time. The research results show that the disaster communication strategy of BPBD is carried out thru direct socialization, education, utilization of communication media, delivery of preventive messages, and community involvement in fire mitigation. The community's response to mitigation messages includes cognitive, affective, and conative aspects. The community generally has a positive understanding and attitude, but the implementation of mitigation behaviors is still not optimal. The research concluded that the disaster communication by BPBD has been quite good, but it requires a more participatory and community-based approach to enhance community preparedness and reduce the risk of fires in East Simeulue.